1982
DOI: 10.2151/jmsj1965.60.4_978
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study of the Effect of CCN on the Size Distribution of Cloud Droplets

Abstract: The effect of the size distribution and chemical composition of cloud condensation nuclei (CCN) on the size distribution of cloud droplets was studied by a numerical model of an adiabatically ascending air-parcel.Specially the formation of a broad droplet size distribution was discussed.Results of computation show that the supersaturation realized in the air-parcel is reduced, a broader size distribution of cloud droplets is produced. If the number concentration of CCN is higher in one air-parcel than that in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
2

Year Published

1993
1993
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 14 publications
1
23
2
Order By: Relevance
“…equation 6), if the aerosol particles consist primarily of two components (e.g., submicrometer particles and supermicrometer mineral dust particles) and if the variabilities in d a,coarse and d a,fine were small. It is also important to investigate the dependence of the d a value of dust particles on their internal mixing state (whether they are coated with solution or not) because the mixing state critically affects its direct radiative effect [Ackerman and Toon, 1981] as well as its cloud microphysical properties; they would activate as cloud condensation nuclei at lower supersaturations [e.g., Takeda and Kuba, 1982] and as ice forming nuclei in the immersion-freezing mode at lower supersaturations and warmer temperatures [Zuberi et al, 2002] when they were coated with solution.…”
Section: Total Aerosol Linear Depolarization Ratiomentioning
confidence: 99%
“…equation 6), if the aerosol particles consist primarily of two components (e.g., submicrometer particles and supermicrometer mineral dust particles) and if the variabilities in d a,coarse and d a,fine were small. It is also important to investigate the dependence of the d a value of dust particles on their internal mixing state (whether they are coated with solution or not) because the mixing state critically affects its direct radiative effect [Ackerman and Toon, 1981] as well as its cloud microphysical properties; they would activate as cloud condensation nuclei at lower supersaturations [e.g., Takeda and Kuba, 1982] and as ice forming nuclei in the immersion-freezing mode at lower supersaturations and warmer temperatures [Zuberi et al, 2002] when they were coated with solution.…”
Section: Total Aerosol Linear Depolarization Ratiomentioning
confidence: 99%
“…However we note that there are other parameters used in this study that can lead to the uncertainties in the results. For example, Takeda and Kuba (1982) found that using an insufficient number of model grids will lead to the narrow CDSD reported by Mordy (1959). Kreidenweis et al (2003) found that both the spectral discretization and the uncertainty in the value of the mass accommodation coefficient can lead to uncertainty in the results.…”
Section: Discussionmentioning
confidence: 99%
“…Takeda and Kuba (1982) noted that the discretizations of Mordy (1959) and Fitzgerald (1974) were too broad to allow an accurate estimation of cloud droplet concentration. In our model, the number of nuclei included in one class is less than 1% of the number of activated cloud droplets.…”
Section: Cloud Modelmentioning
confidence: 99%
“…The equations governing the growth rate of droplets by condensation are those in Takeda and Kuba (1982). The potential temperature tendency of an air parcel is calculated.…”
Section: Governing Equationsmentioning
confidence: 99%
See 1 more Smart Citation